THE RELEVANCE OF EDUCATING PRIMARY EDUCATION STUDENTS BASED ON NATIONAL CONTENT - Mirzaakbarov Abdurasul Mirzaakbarovich (The Conference Hub, 2025)
This article explores the relevance of teaching primary education students using national content. The study employed methods such as literature analysis, questionnaires, and observation to evaluate the impact of national content on the educational process. The findings indicate that national content enhances students’ interest in learning and their sense of national identity; however, its effectiveness requires integration with modern pedagogical approaches. The article analyzes the advantages and limitations of this approach and provides practical recommendations. The research is aimed at advancing primary education and preserving national values.
Keywords: Primary education, national content, student preparation, national values, pedagogical approach, educational effectiveness, cultural heritage, modern technologies.